Zonisamide for the Treatment of Parkinson Disease: A Current Update - Li, Chengqian; Xue, Li; Liu, Yumei; Yang, Zhengjie; Chi, Song; Xie, Anmu (Frontiers in Neuroscience, 2020)
Zonisamide has been used as an add-on treatment in order to overcome the deficiencies of the general therapies currently used to resolve the motor complications and non-motor symptoms of Parkinson’s disease. Various trials have been designed to investigate the mechanism of action and treatment effects of zonisamide in this condition. Most clinical trials of zonisamide in Parkinson's disease were from Japan. The vast majority of studies used changes in the Unified Parkinson's Disease Rating Scale (UPDRS) scores and daily “OFF” time as primary endpoints. Based on adequate randomized controlled trials, zonisamide is considered a safe and efficacious add-on treatment in Parkinson's disease. The most convincing proof is available for a dosage of 25‒50 mg, which was shown to lead to a significant reduction in the UPDRS III score and daily “OFF” time, without increasing disabling dyskinesia. Furthermore, zonisamide may play a beneficial role in improving non-motor symptoms in PD, including impulsive–compulsive disorder, rapid eye movement sleep behavior disorder, and dementia. Among the various mechanisms reported, inhibition of monoamine oxidase-B, blocking of T-type calcium channels, modulation of the levodopa‒dopamine metabolism, modulation of receptor expression, and neuroprotection are the most often cited. The mechanisms underlying neuroprotection, including modulation of dopamine turnover, induction of neurotrophic factor expression, inhibition of oxidative stress and apoptosis, inhibition of neuroinflammation, modulation of synaptic transmission, and modulation of gene expression, have been most extensively studied. This review focuses on structure, pharmacokinetics, mechanisms, therapeutic effectiveness, and safety and tolerability of zonisamide in patients with Parkinson’s disease.